The evolution of the philosophical program of the Frankfurt School’s critical theory - Ratnikova, Irina M. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The evolution of the philosophical discourse of the Frankfurt School’s Critical Theory as one of the most important research program in modern Humanities is studied in this article. The invariant content that provides conceptual integrity and immanent logic in its development from the classical stage (M. Horkheimer, T. Adorno, etc.) to the modern version (A. Honnet, R. Forst, etc.) is explicated.
Keywords: Critical Theory; the Frankfurt School; modernity; communicative action; struggle for recognition; right to justification